MAINTAIN THE VALUES AND DESIGN NEW BUSINESS STRATEGY TO RETAINED CUSTOMER AND POTENTIAL MARKETS (Case Study at Sumber Hidangan Restaurant) - Rintan Saragih (LP2MTBM MAKARIOZ, 2018)
This report was commissioned to examine why the consumers at Sumber Hidangan Cafe still loyal since 1929 and also to understand values and benefit they are looking for. Established since 1929, Sumber Hidangan has retained their own uniqueness which makes them stand out from the rest of the other café and bread store. This research is using qualitative methode through indepth interview and questionnaire by segmenting the market based on demographics, psychographics, psychological influence, social influence, marketplace behavior and consumption behavior to gathered useful information regarding Sumber Hidangan‟s consumer behaviorBased on these research, Sumber Hidangan original taste which still lasting till today without any preservatives, Sumber Hidangan history (colonial building and family memory heritage), as well as the vintage Jl Braga makes a strong appeal to the Sumber Hidangan consumers. From the research we can conclude that values, emotional benefits and functional Benefits offered by Sumber Hidangan was delivered to the consumers. And these is like a strong business strategy developed by Sumber Hidangan